Delali Nutsukpo, Ghana: Agriculture and National Adaptation Planning learning workshop 2013 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
A 2-day workshop hosted by the CGIAR Research Program on Climate Change, Agriculture and Food Security www.ccafs.cgiar.org from 13-14 November, Warsaw, Poland brought together 37 representatives from 10 different countries across Asia, Africa and Latin America to share their lessons and experiences in developing climate adaptation plans for the agriculture sector. Here, Kofi Delali Nutsukpo shares his hopes for the key messages he will bring back with him to Ghana. For more information see: Planning climate adaptation in agriculture http://ow.ly/qSN00 New report highlights lessons from national adaptation planning http://ow.ly/qSN1h